IN-HOSPITAL OUTCOME OF ACUTE MYOCARDIAL INFARCTION IN CORRELATION WITH '˜THROMBOLYSIS IN MYOCARDIAL INFARCTION' RISK SCORE - Masood, Arslan; Naqvi, Moazzam Ali; Jafar, Shariq Sohail; Mufti, Akif Ali; Akram, Zubair (Journal of Ayub Medical College Abbottabad, 2010)
Background: Effective risk stratification is integral to management of acute coronary syndromes (ACS). The Thrombolysis in Myocardial Infarction (TIMI) risk score for ST-segment elevation myocardial infarction (STEMI) is a simple integer score based on 8 high-risk parameters that can be used at the bedside for risk stratification of patients at presentation with STEMI. Objectives: To evaluate the prognostic significance of TIMI risk score in a local population group of acute STEMI. Material and Methods: The study included 160 cases of STEMI eligible for thrombolysis. TIMI risk score was calculated for each case at the time of presentation and were then followed during their hospital stay for the occurrence of electrical and mechanical complications as well as mortality. The patients were divided into three risk groups, namely '˜lowrisk', '˜moderate-risk' and '˜high-risk' based on their TIMI scores (0-4 low-risk, 5-8 moderate-risk, 9-14 high risk). The frequencies of complications and deaths were compared among the three risk groups. Results: Post MI arrhythmias were noted in 2.2%, 16% and 50%; cardiogenic shock in 6.7%, 16% and 60%; pulmonary edema in 6.7%, 20% and 80%; mechanical complications of MI in 0%, 8% and 30%; death in 4.4%, 8%, and 60% of patients belonging to low-risk, moderate-risk and high-risk groups respectively. Frequency of complications and death correlated well with TIMI risk score (p=0.001). Conclusion: TIMI risk score correlates well with the frequency of electrical or mechanical complications and death after STEMI. Keywords: ST elevation MI, Acute Myocardial infarction, Ischemic heart disease